PENGARUH FINANCIAL KNOWLEDGE DAN FINANCIAL ATTITUDE TERHADAP FINANCIAL BEHAVIOR PADA YOUTH ENTREPRENEUR KOTA MALANG - Sandi, Kemal; Worokinasih, Saparila; Darmawan, Ari (FIA UB, 2020)
The ability to manage finances is able to have an affect the financial condition of individuals and business organizations in the future. The study aims to determine the impact of financial knowledge on financial behavior and the role of financial attitude on financial behavior and also its role as a mediator between the relationship of financial knowledge and financial behavior. This study was conducted by collecting and analyzing journals related to the research objectives. Based on the literature study conducted, financial knowledge has an effect on financial attitude and financial behavior. Financial attitude has a positive impact on financial behavior and positively moderates the relationship between financial knowledge and financial behavior.